The Implementation of IDA* Algorithm to Translate Words From Indonesian Language Into Sundanese - Harahap, Aninda Muliani; Sibuea, David Arnold; Cefri, Ray; Stepane, Ruth (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Sundanese are tribes from West Java and Banten that use their own local language known as Sundanese. The large number of local residents who still use Sundanese in communicating daily is an obstacle in increasing tourist visits to the area. Then a translator is needed which can be used as a liaison between tourists and local residents so that there is no miscommunication between the two. But the increasing number of tourists, there is a lack of the number of translators needed, so it needs to be made a translator application by utilizing the development of computer technology. The application developed is an Indonesian-Sundanese to translate in the form of words using the IDA* algorithm. This algorithm is an A* algorithm whose depth is limited to each search iteration. Although the time complexity is higher than that of the A* algorithm, the IDA* algorithm does not require as much memory as needed by the A* algorithm. Then the IDA* algorithm is used in this study. The results of this study indicate that the IDA* algorithm can be implemented to convert translate words in Indonesian and Sundanese based on the estimation value of the smallest total cost of each word stored in the database, where the word that has the smallest total cost estimationcan be selected as a result of the translation.